Produksi Bio-Oil dari Rumput Gajah dengan Fast Pyrolysis menggunakan Circulating Fluidized Bed Reactor (CFBr) dengan Kapasitas 45 Kg/H - Ilham Mufandi; W. Treedet; P. Singbua; R. Suntivarakorn (CHEMICA: Jurnal Teknik Kimia, 2018)
The objective of this work was to produce the renewable liquid fuel (Bio-oil) form Napier grass by fast pyrolysis in a circulating fluidized bed reactor. The experiment was conducted to improve the bio-oil production (pyrolysis oil) using the condenser. Circulating fluidized bed reactor had a height of 4.5 m, sand as bed material with a diameter 249 nm and Napier grass as the raw material for bio-oil production. The parameter in this work compared with previous research. The experiment was carried out at different temperature ranging from , Â dan ; feed rate biomass at 45 kg/h and a superficial velocity 7 m/s. The experimental result shown that the maximum yield was 39.60 % at pyrolysis temperature of 480 Â as the best temperature. While the bio-char production and Non condensable gas (NCG) was at 10.67% and 49.73%. Respectively, these results indicated that the condenser can be improve the bio-oil production yield in the system. Furthermore, the condenser process has been shown to have a direct effect on the bio-oil yield.